2004
DOI: 10.1109/tbme.2004.836522
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Nonplanar Microelectrode Array Circuits for Use in Arthroscopic Diagnosis of Cartilage Diseases

Abstract: Abstract-A process to fabricate nonplanar microelectrode array circuits was developed and the microelectrodes were characterized. These platinum microelectrode arrays are for recording streaming potential signals generated during indentation of articular cartilage. The nonplanar substrate was produced by permanent deformation of a 7-in-diameter circular stainless-steel wafer to form 32 semi-spherical caps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Berkenblit et al (1994) proposed that techniques for detection of the electrokinetic properties were useful for nondestructive measurement of osteoarthritis. Quenneville et al (2004) developed a microelectrode array device for the detection of the streaming potential during diagnosis of the state of cartilage. These studies indicated that load-bearing tissue such as cartilage and discs could be evaluated using streaming potential measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Berkenblit et al (1994) proposed that techniques for detection of the electrokinetic properties were useful for nondestructive measurement of osteoarthritis. Quenneville et al (2004) developed a microelectrode array device for the detection of the streaming potential during diagnosis of the state of cartilage. These studies indicated that load-bearing tissue such as cartilage and discs could be evaluated using streaming potential measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Two reservoirs, inner and outer, were filled with phosphate buffered saline solution (0.145 M, pH 7.3 [16,17]. The two reservoirs were connected by the sample.…”
Section: Methodsmentioning
confidence: 99%
“…For phase shift lithography, it would be quite difficult to engineer the phase mask to correct for the mechanical deformations, and thus elimination of the distortions would likely require manipulation of the exposure conditions. [22] Advances in microfabrication, namely in the area of nonplanar electronic devices, such as curved photodiode arrays for solar cell applications and synthetic retinal implants, [36][37][38][39][40] demand the ability to pattern metals, and other materials with electrical functionality, on geometrically diverse surfaces. The aforementioned fabrication methods are intended to replace traditional contact lithography by finding novel ways to use PDMS as a patterning element.…”
mentioning
confidence: 99%